2007
DOI: 10.1146/annurev.immunol.25.022106.141706
|View full text |Cite
|
Sign up to set email alerts
|

The Immunobiology of SARS

Abstract: Severe acute respiratory syndrome (SARS) presented as an atypical pneumonia that progressed to acute respiratory distress syndrome in approximately 20% of cases and was associated with a mortality of about 10%. The etiological agent was a novel coronavirus (CoV). Angiotensin-converting enzyme 2 is the functional receptor for SARS-CoV; DC-SIGN and CD209L (L-SIGN) can enhance viral entry. Although the virus infects the lungs, gastrointestinal tract, liver, and kidneys, the disease is limited to the lungs, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
277
1
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(299 citation statements)
references
References 175 publications
14
277
1
6
Order By: Relevance
“…PRCV infection in pigs has previously been suggested as a good model for studying the effect of corticosteroids on severe acute respiratory syndrome coronavirus (SARS-CoV) infection in humans [46]. Chen and Subbarao have done an extensive summary on currently available knowledge of SARS immunobiology [47]. Despite the fact that SARS-CoV causes severe illness in humans and is lethal in 10% of the cases, in contrast to PRCV in pigs, which is usually mild or subclinical, there are some similarities between the courses of these two infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PRCV infection in pigs has previously been suggested as a good model for studying the effect of corticosteroids on severe acute respiratory syndrome coronavirus (SARS-CoV) infection in humans [46]. Chen and Subbarao have done an extensive summary on currently available knowledge of SARS immunobiology [47]. Despite the fact that SARS-CoV causes severe illness in humans and is lethal in 10% of the cases, in contrast to PRCV in pigs, which is usually mild or subclinical, there are some similarities between the courses of these two infections.…”
Section: Discussionmentioning
confidence: 99%
“…Both PRCV and SARS-CoV seem to target predominantly type 2 pneumocytes in the lungs [50,51]. Conflicting reports on the ability of SARS-CoV to infect macrophages have been discussed in the above mentioned review article [47]. There is still very limited information about the induction of cytokines by SARS-CoV in the lungs of humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been identified that a metallopeptidase, angiotensin-converting enzyme 2, is a functional receptor for severe acute respiratory syndrome coronavirus infection [115], other reports have demonstrated that DC-SIGN, L-SIGN (also called CD209L, specific for liver/lymph node) [116][117][118][119], and heparan sulphate [120] also are involved in the virus pathogenesis. Thus, there are reasons to believe that lactoferrin could prevent severe acute respiratory syndrome coronavirus spread in the host through the same mechanism as described for human immunodeficiency virus, by interacting with DC-SIGN or heparan sulphate receptors.…”
Section: Binding To Structural Virus Proteins Prevent Virus Host Cellmentioning
confidence: 99%
“…A pentapeptide ( -casochemotide-1) with amino acid sequence (YPVEP) matching an actinase E digest peptide from bovinecasein (corresponding to fraction [114][115][116][117][118], has been tested and demonstrated to both chemoattract and activate, human and mouse monocytes and macrophages by using a unique G-protein coupled receptors [142].…”
Section: Table 3 Milk Proteins-derived Peptides With Antiviral and Imentioning
confidence: 99%